Chromosomal and Extrachromosomal Instability of the cyclin D2 Gene is Induced by Myc Overexpression - Mai, Sabine (Stockton Press, 1999)
We examined the expression of cyclins D1, D2, D3, and E in mouse B-lymphocytic tumors. Cyclin D2 mRNA was consistently elevated in plasmacytomas, which characteristically contain Myc-activating chromosome translocations and constitutive c-Myc mRNA and protein expression. We examined the nature of cyclin D2 overexpression in plasmacytomas and other tumors. Human and mouse tumor cell lines that exhibited c-Myc dysregulation displayed instability of the cyclin D2 gene, detected by Southern blot, fluorescent in situ hybridization (FISH), and in extrachromosomal preparations (Hirt extracts). Cyclin D2 instability was not seen in cells with low levels of c-Myc protein. To unequivocally demonstrate a role of c-Myc in the instability of the cyclin D2 gene, a Myc-estrogen receptor chimera was activated in two mouse cell lines. After 3 to 4 days of Myc-ER(Tm) activation, instability at the cyclin D2 locus was seen in the form of extrachromosomal elements, determined by FISH of metaphase and interphase nuclei and of purified extrachromosomal elements. At the same time points. Northern and Western blot analyses detected increased cyclin D2 mRNA and protein levels. These data suggest that Myc-induced genomic instability may contribute to neoplasia by increasing the levels of a cell cycle-regulating protein, cyclin D2, via intrachromosomal amplification of its gene or generation of extrachromosomal copies.